Internal Factor Difference That Affects University Students’ Academic Dishonesty Inside and Outside of JABODETABEK - Salma, Hasna Hafizhah; Brata Winardy, Gary Collins; Septiana, Eva (Psychological Research on Urban Society, 2023)
Urban society shown a more heterogenous personal quality compared to rural society such as greater diversity in social status and religious pluralism. Unfortunately, structure of urban society tends to put achievement above morality in academic practices. This can be seen in academic phenomenon such as cheating, and plagiarism. Such practices are only made easier through technology. Since the emergence of Covid-19 pandemic the use of technology is increasing substantially in learning process. In urban region such as Jakarta metropolitan area, Indonesia, the use of internet and technology in university become one of many factors that facilitate academic dishonesty behaviors. This research is quantitative research with samples of 187 university students currently taking courses on associate degree, bachelor, and master’s degree from public and private universities inside and outside of Jakarta metropolitan area (JABODETABEK). The result showed differences in proportion of internal factor variance that includes religious commitment, self-efficacy, and self-monitoring. Participants in Jakarta metropolitan area are controlled more by internal factors to abstain from academic dishonesty, compared to students outside of Jakarta metropolitan area. These findings can give consideration for universities stakeholders to enact an academic climate that supports integrity with character development, especially in urban universities.